AM1241-Loaded Poly(ethylene glycol)–Dithiothreitol Hydrogel Repairs Cranial Bone Defects by Promoting Vascular Endothelial Growth Factor and COL-1 Expression - Ai, Yilong; She, Wenting; Wu, Siyuan; Shao, Qing; Jiang, Ziran; Chen, Pengcheng; Mei, Li; Zou, Chen; Peng, Youjian; He, Yan (Frontiers in Cell and Developmental Biology, 2022)
Objective: To explore the repair effect of the prepared drug-loaded AM1241 poly (ethylene glycol) - dithiothreitol (PEG-DTT) hydrogel on cranial bone defects in SD rats. Methods: The PEG-DTT hydrogel under borax catalysis was quickly prepared, and the characterization of the material was observed by scanning electron microscope. The effect of AM1241 on cell activity and bone tissue differentiation was tested. The SD rat model of cranial bone defect was established, and the defect was repaired by injecting the prepared hydrogel into the defect. The defect was divided into 4 groups, namely sham group, blank group, PEG-DTT group and PEG-DTT + AM1241 group. The rats were euthanized, and whole cranial bone was taken out for micro-CT and histological observation. Results: The prepared hydrogel is porous, it is liquid when heated to 80 °C, and a hydrogel when cooled to 25 °C. 5-10M AM1241 increased osteoblast activity. A moderate amount of AM1241 can promote osteogenic differentiation. Both the PEG-DTT group and PEG-DTT + AM1241 group showed obvious new bone tissue formation, but the PEG-DTT+AM1241 group had better effect. In addition, the new bone tissue in the PEG-DTT+AM1241 group was significantly more than that in the other groups. Conclusion: The prepared AM1241-loaded PEG-DTT hydrogel showed good repair effect on SD rats with cranial bone defects. It can be used as materials for cranial bone repair in SD rats with cranial bone defects, but the repair effect is weaker than that of normal bone. These results provide a theoretical and practical basis for its further clinical application.